Burns among older persons: A narrative review - Jonathan Bayuo; Anita Esi Botchway (Elsevier, 2017)
Background: The older adult population has been noted to be increasing at a steady rate and they have been described as persons at a high risk of being involved in burns. Thus, attention towards trauma among older adults is on the rise and there is a need to understand the characteristics of the injury among this population group. Methods: A narrative review approach was utilised for the study. PubMed, ScienceDirect and Google Scholar were used as search engines to identify studies that focused on burns in older adults or discussed some aspects related to the phenomenon from January 2000 to January 2017. Results: In all, thirty one (31) articles were retrieved. The terms "older adult" and "elderly" was noted to exist in literature with varying age limits. Older persons were noted to form a substantial number of persons affected by burns with flame burn identified as the major type of burns affecting older adults. However, scald burns were recognised to be higher among older females than males. Majority of these injuries were noted to occur within the domestic settings and associated with cooking. The presence of co-morbid factors was reported in most studies with hypertension and diabetes recorded as the commonest. The existence of dementia was noted to be associated with severe burns and double length of hospital stay. Outcomes of the injury included varying mortality rates, worsening of existing premorbid conditions, respiratory complications such as pneumonia and longer hospital stay. The use of a frailty scoring system was noted to offer better outcome prediction as compared to only the chronological age. One study noted that females experienced longer hospitalisation periods as compared to elderly males even though their burns were smaller. Conclusion: Older persons are affected by burns and resources required to meet their needs may be higher due to their longer periods of hospitalisation. The domestic nature of their injuries provides a window of opportunity to design preventive strategies. Also, policies and strategies are needed to protect the well-being of older persons. Further studies are needed to clearly understand gender differences associated with burns as this can impact management strategies. Follow up strategies after discharge need to be considered to understand the outcomes overtime. Also, more prospective studies and randomised control trials are needed in understanding the effectiveness of various interventions used in the clinical management of older persons. Keywords: Older persons, Burns, Incidence, Aetiology